Efficacy of afatinib or osimertinib plus cetuximab combination therapy for non-small-cell lung cancer with EGFR exon 20 insertion mutations. (January 2019) - Hasegawa, Hanako; Yasuda, Hiroyuki; Hamamoto, Junko; Masuzawa, Keita; Tani, Tetsuo; Nukaga, Shigenari; Hirano, Toshiyuki; Kobayashi, Keigo; Manabe, Tadashi; Terai, Hideki; Ikemura, Shinnosuke; Kawada, Ichiro; et al.
Highlights: Ba/F3 cells with EGFR exon 20 insertion mutations were used in vitro and in vivo. Cetuximab can increase the effect of afatinib or osimertinib against these mutations. These combination treatments were well tolerable in vivo . Abstract: Objectives: Epidermal growth factor receptor (EGFR) mutation-positive lung cancer accounts for a significant subgroup of non-small cell lung cancers (NSCLC). Approximately 4–10% of EGFR mutations in NSCLC are EGFR exon 20 insertion mutations, which are reportedly associated with resistance to EGFR tyrosine kinase inhibitor (EGFR-TKI) treatment. NSCLC patients carrying these mutations are rarely treated with EGFR-TKIs. The purpose of this study was to evaluate the efficacy of afatinib or osimertinib plus cetuximab combination therapy in experimental NSCLC models with EGFR exon 20 insertion mutations. Materials and methods: The EGFR mutations examined in this study were A763_Y764insFQEA, Y764_V765insHH, A767_V769dupASV, and D770_N771insNPG. Ba/F3 cells constitutively expressing wild type or mutated EGFR were used to determine the efficacy of afatinib or osimertinib plus cetuximab combination therapy in vitro . To determine the efficacy of the combination therapy in vivo, female BALB/c-nu mice were injected subcutaneously with 1 million Ba/F3 cells carrying EGFR A767_V769dupASV or Y764_V765insHH. Results: We observed a mild but significant (P < 0.05) additive effect of the combination therapy against several EGFR exon 20 insertion mutations in vitro. Regarding EGFR A767_V769dupASV and EGFR Y764_V765insHH, cetuximab and afatinib single treatment did not induce significant inhibition of tumor formation; however, afatinib plus cetuximab combination treatment induced significant (P < 0.05) tumor growth inhibition without significant body weight loss or skin rash. Conclusion: The combination therapy induced a more potent inhibitory effect against several EGFR exon 20 insertion mutations than either therapy alone. Cetuximab can potentially increase the efficacy of afatinib or osimertinib in NSCLC with EGFR exon 20 insertion mutations.